Nodal expression in triple-negative breast cancer: Cellular effects of its inhibition following doxorubicin treatment. Issue 9 (2nd May 2016) - Bodenstine, Thomas M.; Chandler, Grace S.; Reed, David W.; Margaryan, Naira V.; Gilgur, Alina; Atkinson, Janis; Ahmed, Nida; Hyser, Matthew; Seftor, Elisabeth A.; Strizzi, Luigi; Hendrix, Mary J. C.
ABSTRACT: Triple-negative breast cancer (TNBC) represents an aggressive cancer subtype characterized by the lack of expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). The independence of TNBC from these growth promoting factors eliminates the efficacy of therapies which specifically target them, and limits TNBC patients to traditional systemic neo/adjuvant chemotherapy. To better understand the growth advantage of TNBC – in the absence of ER, PR and HER2, we focused on the embryonic morphogen Nodal (associated with the cancer stem cell phenotype), which is re-expressed in aggressive breast cancers. Most notably, our previous data demonstrated that inhibition of Nodal signaling in breast cancer cells reduces their tumorigenic capacity. Furthermore, inhibiting Nodal in other cancers has resulted in improved effects of chemotherapy, although the mechanisms for this remain unknown. Thus, we hypothesized that targeting Nodal in TNBC cells in combination with conventional chemotherapy may improve efficacy and represent a potential new strategy. Our preliminary data demonstrate that Nodal is highly expressed in TNBC when compared to invasive hormone receptor positive samples. Treatment of Nodal expressing TNBC cell lines with a neutralizing anti-Nodal antibody reduces the viability of cells that had previously survived treatment with the anthracycline doxorubicin. We show that inhibiting Nodal may alter response mechanisms employed by cancer cells undergoing DNA damage. These data suggest that development of therapies which target Nodal in TNBC may lead to additional treatment options in conjunction with chemotherapy regimens – by altering signaling pathways critical to cellular survival.